La création d'une iconographie sivaïte narrative Incarnations du dieu dans les temples pallava construits - Gillet, Valérie (Collection Indologie, 2010)
At the end of the 7th century, the Pallava dynasty began to construct the first temples built entirely of stone in the Tamil-speaking South. For the most part these were dedicated to Śiva and their walls are thus adorned with representations of him in various embodiments, some benign, some fierce and sanguinary, others victorious and regal. A lengthy introduction presents the historical and religious contexts in which this imagery was conceived and flourished. Each chapter of the book is then devoted to one of the principal forms of Śiva, and the concluding chapter attempts to outline the iconographical program of a Śaiva sanctuary in the Pallava period. Because narrative Śaiva art was not widely developed by this time, the illustration of many deeds of Śiva had still to be invented. It is therefore the creation of an iconography that we see in Pallava monuments, an iconography inspired both by pan-Indian mythology and by local traditions, borrowing at the same time elements from various religious movements. If some Pallava representations both appear and disappear with the dynasty, most of them were long to exert influence on subsequent South Indian sculptural art. Thus narrative Pallava sculpture appears to stand at the point of origin of a long and now deeply rooted tradition.